THE EFFECT OF PROFITABILITY, LEVERAGE, AND LIQUIDITY ON TAX AVOIDANCE (EMPIRICAL STUDY ON MINING SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE) - Kristina, Yeni Wasianti (Jurnal KIAFE, 2022)
The author's interest in conducting this study is based on the results of the Tax Justice Network's publication in The State of Tax Justice 2021 Report which states that countries lose $483 billion in taxes per year due to the misuse of global taxes by multinational companies and individuals who hide assets and income streams abroad. This study aims to determine the effect of profitability, leverage, and liquidity on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange partially or simultaneously. The method used in the selection of samples was purposive sampling and obtained 30 samples from 63 companies that had met the sample criteria. The analysis method used in this study is multiple linear regression analysis with the help IBM SPSS 25. The results showed that profitability is negative and insignificant to tax avoidance, while leverage and liquidity have a positive and significant effect on tax avoidance. Simultaneously profitability, leverage, and liquidity have a significant effect on tax avoidance.